Visual Aurality in Russian Modernist Experiments: Explorations in Synesthesia and Auditory Imagination - Listengarten, Julia (Recherches sémiotiques / Semiotic Inquiry, 2015)
Russian modernist experiments in sensory communication include the interplay of sound and light in Alexander Scriabin’s symphonic mysteries as well as colored sounds in Wassily Kandinsky’s stage compositions. Inspired by various philosophical principles and creative methodologies, these artists explored the dialogue between the aural and the visual and its potential to influence the creative process and impact audience perception. This article seeks to assess the role of music and sound in synesthetic experiments of Scriabin and Kandinsky and place their theory and practice within the larger philosophical, artistic, and scientific contexts of their period and beyond.